A Bibliometric Analysis of the Annual Meeting Proceedings of the Association for Information Science and Technology. Issue 1 (13th October 2021) - Agarwal, Naresh Kumar; Islam, Md Anwarul
Abstract: In this study, we analyzed two decades of the proceedings of the Association for Information Science & Technology (ASIS&T) to uncover bibliometric patterns. We found 3, 129 publications from 2000–2020, with more than three‐quarters jointly authored. Most authors are from U.S., Canada, and China. Social media and information behavior are the top‐researched areas. The top‐cited journals are the Journal of the Association for Information Science & Technology, Information Processing and Management, and Library and Information Science Research. The findings affirm ASIS&T's move to an international association and point to the growing importance of collaborative work and social media. The study fills the gap in the analysis of ASIS&T conference proceedings and will help information professionals understand patterns in recent research. This should help guide them in their future research directions.